Efeito da irradiação do laser arseneto de gálio (gaas; 904 nm) na regeneração de músculos esqueléticos de camundongos - Gutiérrez, Rita Mara Soares (2010)
Musculoskeletal injuries are one of the clinical cases more routinely found in physical therapy practice. Soon after a muscle injury, there are tissue necrosis and activation of an inflammatory response and the following activation of satellite cells that are mainly responsible for the regenerative process of the skeletal muscle. Despite that regenerative process of the skeletal muscle has been widely studied for the past decades, there are still several points to be investigated, especially the ones regarding the possible therapeutic agents able to improve muscle regeneration. The goal of this work was to verify the effect of GaAs laser (904 nm) operating in pulsed mode with medium intensity of 5MW, peak power of 15 W, power density of 71.43 MW/cm2 and beam area of 0.07 cm2. Thirty C57B16 3-month-old male mice weighing approximately 25 g were used. The mice were injured after intramuscular injection (in the left anterior tibial muscle, TA) of crotoxin (CTX) and received irradiation with GaAs laser at doses of 1.5 J or 3 J in the TA muscle from the 3rd day after the injury and went on to the 8th day, when they were sacrificed. A group of house mice was only injected with CTX and assessed after 8 days. Additionally, we performed the control groups only treated with laser at doses of 1.5 J and 3 J and the control group injected only with saline (NaCl 0.9%). The TA muscles were weighed, pre-frozen in isopentane and stored in liquid nitrogen until the analysis. The muscle injured with CTX and treated with laser at dose of 3 J showed muscle fibers in regeneration with centralized nucleus marked with MHCn and cross sectional area bigger than that from the group that was only injured (45%, p< 0.05). In summary, our results suggest that GaAs laser of 904 nm at the dose of 3 J applied once a day directly to the skin of the injured skeletal muscle of the mice, starting from the third day after the injury, during five consecutive days is an efficient method to improve muscle regeneration.